Uji Aktivitas Antibakteri Ekstrak Kulit Jeruk Kalamansi (Citrofortunella microcarpa bunge) Pada Bakteri Propionibacterium Acnes - Saputri, Nur Arida; Darsono, Putri Vidiasari; Mahdiyah, Dede; Audina, Mia (LPPM Universitas Sari Mulia, 2025)
Background: Acne or acne vulgaris is an inflammatory disease that often occurs in the facial area. Usually characterized by the appearance of small reddish or yellow lumps (because they contain pus). The main organism that causes acne is Propionibacterium acnes. The growth of Propionibacterium acne bacteria can be controlled with antibacterials and plants that contain secondary metabolite compounds including flavonoids, alkaloids, saponins, steroids and tannins. One of the plants that contains secondary metabolites is calamansi orange peel. Objective: This study aims to determine the antibacterial activity of calamansi orange peel extract (Citrofortunella microcarpa Bunge) against Propionibacterium acnes bacteria through MIC and KBM testing. Method: This type of research is a true experimental method with post test only with control group design. Results: Antibacterial testing using the disc diffusion method on calamansi orange peel extract (Citrofortunella microcarpa Bunge) resulted in an inhibition zone of 22.02 mm, while MIC testing with concentrations of 5%, 7,5% and 10% resulted in inhibiting the growth of Propionibacterium acnes bacteria. while KBM did not produce results. The results of the Kruskal Wallis statistical test of 0.007 and Mann Whitney of 0.025 showed a p value <0.05, indicating that there was a significant difference between the extract concentration groups and there was a difference in the increase in the results of the bacterial activity test that received the extract treatment. Conclusion: Calamansi orange peel extract (Citrofortunella microcarpa Bunge) against Propionibacterium acnes bacteria has inhibitory power at concentrations of 50%, 75% and 100% but does not have killing power.